High long-term absolute risk of recurrent venous thromboembolism in patients with hereditary deficiencies of protein S, protein C or antithrombin - Brouwer, Jan-Leendert P.; Lijfering, Willem M.; Kate, Min Ki ten; Kluin-Nelemans, Hanneke C.; Veeger, Nic J. G. M.; van der Meer, Jan (Thrombosis and Haemostasis, 2009)
Hereditary deficiencies of protein S, protein C and antithrombin are known risk factors for first venous thromboembolism. We assessed the absolute risk of recurrence, and the contribution of concomitant thrombophilic defects in a large cohort of families with these deficiencies. Annual incidence of recurrence was estimated in 130 deficient patients, with separate estimates for those with each of protein S, protein C, and antithrombin deficiency, and in eight non-deficient patients with prior venous thromboembolism. All patients were also tested for factor V Leiden, prothrombin G20210A, high levels of factors VIII, IX and XI, and hyperhomocysteinemia. There were 81 recurrent events among 130 deficient patients. Median follow-up was 4.6 years. Annual incidences (95% confidence interval) of recurrent venous thromboembolism were 8.4% (5.8–11.7) for protein S deficiency, 6.0% (3.9–8.7) for protein C deficiency, 10.0% (6.1–15.4) for antithrombin deficiency, and overall 7.7% (6.1–9.5). Relative risk of recurrence in patients with a spontaneous versus provoked first event was 1.5 (0.95–2.3). Cumulative recurrence rates at 1, 5 and 10 years were 15%, 38% and 53%. Relative risk of recurrence with concomitant defects was 1.4 (0.7–2.6) (1 defect) and 1.4 (0.8–2.7) (≥2 defects). Annual incidence was 1.0% (0.03–5.5) in eight non-deficient patients. Annual incidence of major bleeding in deficient patients on oral anticoagulant treatment was 0.5% (0.2–1.0). We conclude that patients with a hereditary protein S, protein C or antithrombin deficiency appear to have a high absolute risk of recurrence. This risk is increased after a first spontaneous event, and by concomitance of other thrombophilic defects.
Keywords: Epidemiology; recurrent venous thromboembolism; thrombophilia